Improving threshold voltage and on/off current ratio of single-walled carbon nanotube field-effect transistor by post-sonication treatments - Ordokhani, Fereshteh; Yedikardes, F. Beyza; Kurt, Ece; Akkan, Nihat; Karatepe, Nilgun; Zayim, Esra; Altun, Mustafa (Elsevier BV, 2021)
Abstract In the process of solution-based fabrication of Single-walled Carbon Nanotube Field Effect Transistor (SWCNT FET), the quality of SWCNTs network plays an important role. SWCNTs networks have disorders and defects because of chirality mismatches that cause the weaker tunneling between SWCNTs, hence suppressing conductance and the electrical performance of the device. In this paper, we present a study on the impact of SWCNTs network structure, which were formed in the channel on the prefabricated test chips, on electrical characteristic parameters like threshold voltage (VT) and on/off current ratio (ION/IOFF). Also, we propose a simple and low-cost post-process to decrease the VT and enhance ION/IOFF of SWCNT FET comparable to the reasonably good performances of the same devices to the date. Post-sonication treatments of the devices in the deionized water and the isopropyl alcohol not only removed the residual impurities remained between individual SWCNTs and around their surface and substrate, but also decreased the structural defects of their network (based on the provided Raman spectroscopy results). This improves ION/IOFF up to 153 times and shifts VT in the negative direction up to almost 0 V. The results indicate the importance of the improvement of SWCNTs network structure in enhancing SWCNT FET electrical performance.